Defacing Memory: (Un) tying Peru’s Memory Knots - Milton, Cynthia E. (2015)
This article examines opposing currents in Peru’s collective memory of their bloody internal war (1980-2000) through an analysis of acts of vandalism perpetrated against one of the country’s few sites of memory, El ojo que llora, in Lima. ‘Vandalism’ in this article is understood as a form of writing (though a violent one) of an alternative vision of the past. Originally intended as a space for remembering and paying homage to the victims of the armed conflict, the site has become a space for contesting memories. As a site of performance of memory and human rights claims, and especially as the target of continued defacement, El ojo que llora has become a stage on which the presence of the past —in its still-conflictual strains— is made visible for national and international publics. It thus refuses the very closure that government narratives would impose, and thereby keeps open public engagement with the past. The ongoing conflicts over the past made visible at this site point to the struggles to define an overarching memory, and in the processthe very meaning of ‘victim’ is constrained.